Sur une Lectura Dantis erronée: Photin de Théssalonique ou de Sirmium? - Stojkovski, Boris (Verbum – Analecta Neolatina, 2016)
The paper analyzes a part from Dante's Inferno (11.8–9) where the name of Photinus is mentioned as a heretic who misled pope Anastasius. The most famous medieval interpreters of Dante Alighieri and his work, Guido da Pisa and, especially, Giovanni Boccacio put forth an incorrect explanation stating that the Photinus Dante mentions was a deacon of Thessalonica. In reality, the explanation provided by those two lectores Dantis is wrong since it was a fourth-century bishop from Syrmia (Sirmium) who had been condemned as heretic. Even though some translators and later interpreters of Dante noticed this, there has not been a detailed analysis of these verses of Inferno.